Coaching strategies while teaching life skills : multiple case study of Estonian youth coaches - Kivinukk, Elina (2014)
Positive youth development and learning life skills through sports have lately gained attention in Europe and Northern America, now the phenomenon needs to be studied in Estonia, having special focus on youth coaches. The purpose of the study was to explore the coaching strategies Estonian coaches use while teaching life skills. The four sub-topics investigated were coaching strategies, coach education, the development of coaching philosophies and intentionality in teaching life skills.